Thermal Expansion Studies on the Spin‐Liquid‐Candidate System κ‐(BEDT‐TTF)2Ag2(CN)3. Issue 9 (18th February 2019) - Hartmann, Steffi; Gati, Elena; Yoshida, Yukihiro; Saito, Gunzi; Lang, Michael
Abstract : This paper presents results of the thermal expansion coefficient of the newly‐synthesized spin‐liquid‐candidate system κ‐(BEDT‐TTF)2 Ag2 (CN)3 . The main finding includes pronounced broad extrema in the electronic contribution to the thermal expansion at T ≈ 18 K along all three crystallographic directions which is assigned to the effect of strong electronic correlations. The observed anomalies are qualitatively consistent with recent theoretical results based on the Hubbard model on a triangular lattice (J. Kokalj and R. H. McKenzie, Phys. Rev. B91, 205121 (2015)). The directional anisotropy of the anomalies implies a ratio of the hopping integrals t′ / t  < 1, where t′ is directed along the b axis. Furthermore, not any indications for a phase transition are found down to low temperatures ( T  ≥ 1.5 K). This observation is in marked contrast to the behavior revealed for the related spin‐liquid‐candidate system κ‐(BEDT‐TTF)2 Cu2 (CN)3 where a mysterious, still unexplained anomaly shows up at 6 K. Abstract : The authors present results of the thermal expansion coefficient of the spin‐liquid‐candidate system κ‐(BEDT‐TTF)2 Ag2 (CN)3 . Their main finding includes broad extrema below T  < 20 K which is assigned to the effect of strong electronic correlations. The observed anomalies are qualitatively consistent with recent theoretical results. The directional anisotropy of the anomalies implies a ratio of the hopping integrals t ′/ t  < 1.